HIDROLISIS GELATIN TULANG IKAN KAKAP MENGGUNAKAN LARUTAN ASAM (The Hydrolysis Gelatin of Kakap Fish Bone Using Acid Solution) - Mulyani, Tri; HP, Sudaryati; Rahmawati, Siska F (REKAPANGAN, 2011)
Gelatin is  a natural  product obtained by hydrolysis  of collagen, a soluble protein, which acts  as the  gelling agent. In  general, the  process  of making gelatin begins  with soaking the bone  in  acid  solution,  aimed  at  dissolving  calcium  phosphat  and  other  mineral  salts.  This treatment resulted  in changes to the texture bone , so that bones become relatively non-rigid. Type of acid used is strong acids, namely HCl, H2SO4 and H3PO4, with the level of 3% - 6% concentration. The  purpose of  this  study  was to determine  the  type and  concentration  of acid as a soaking solution. The result showed that the best treatment was HCL concentration of 3%, with  water  content  6.54%,  ash  3.27%, 77.92% protein, gel  strength 72.07  bloom, viscosity 17.86 cp, pH 4.88 and  yield 14.03%. Key words : gelatin, collagen, bone, hydrolysis